Determinants of Price Earnings Ratio: A Study in Manufacturing Companies - Gabriel Angga; Elizabeth Sugiarto Dermawan (International Journal of Application on Economics and Business, 2023)
The purpose of this study was to see how the Dividend Pay-out Ratio, Profitability as measured by Return on Equity, Leverage as measured by Debt to Asset Ratio, and Earning Growth affected Firm Value as measured by Price Earnings Ratio in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. Non-probability sampling with a purposive sampling methodology was utilized with a sample of 51 companies, and the SPSS for Windows 25 application was used to aid with data analysis. Dividend Pay-out Ratio and Earning Growth have a positive and significant effect on Price Earnings Ratio, Return on Equity has a positive and insignificant effect on Price Earnings Ratio, and Debt to Asset Ratio has a negative and significant effect on Price Earnings Ratio, according to the findings of this study.